The Effect of Brand Trust as Extrinsic Characteristics on Young Consumers’ Product Preferences: An Experimental Study - Gulnil Aydin; Aybeniz Akdeniz Ar; Elif Dogan Savas (European Scientific Journal, ESJ, 2018)
Purpose: This study was carried out in order to be able to evaluate the effects of intrinsic (quality, taste, smell, etc.) and extrinsic (brand, packaging, country of origin, etc.) characteristics in product preferences and quality perceptions and to understand the importance of brand trust as an extrinsic characteristic in preferences. Design / Methodology: In the study, the evaluations of the university students about the intrinsic and extrinsic characteristics of the cocoa hazelnut cream brands were investigated. In the experimental study with the participation of 50 students, the effects of the intrinsic and extrinsic characteristics on product preferences and quality perceptions were evaluated with the help of the blind and visibility tests applied to participants. Findings: As a result of the research, it was seen that participants changed their evaluations positively after seeing the brand, which they trust, regarding to the intrinsic characteristics evaluations that they have made without seeing the brand and the package and they diversified their perceptions positively regarding to the intrinsic characteristics for the brands that they trust and like the packaging. Research Limitations / Implications: The fact that the number of samples taken for the research in the experimental studies is not too high is a constraint on the evaluation of the results. For this reason, the basic suggestion for future studies is to conduct the research with a wider number of the samples. Originality / Value: This experimental study is important as it reveals the result that the perceptual factors remain at the forefront for the customers about food products.